The Effects of Inner and Outer Green Supply Chain and Eco-Drawing on the Environmental Sustainability in Indonesia - Prasetyo Iswahyudi; Dewie Tri Wijayati; Soedjarwo Soedjarwo; Sugi Hartono (International Journal of Supply Chain Management, 2020)
Abstract-The growing attention towards the supply chain due to the extensive achievements of organizational goal is the motivation of this study. Thus, the goal associated with this article is to explore the links of inner and outer green supply chain management (GSCM) and eco-drawing on the environmental sustainability in Indonesia. The goals also consist the mediating role of government elasticity among the links of inner and outer GSCM, eco-drawing and environmental sustainability. The data were gathered from the workers of the quality management department with the help of questionnaires and analyzed the data by PLS-SEM. The findings show that inner and outer GSCM and eco-drawing have positive link with the environmental sustainability. The results also show that government elasticity has positive mediation among the nexus of inner and outer GSCM, eco-drawing and environmental sustainability. This study is suitable for the policymakers while making the policies regarding environmental sustainability along with GSCM and firm performance.